Fluorescent carbon dots directly derived from polyethyleneimine and their application for the detection of Co2+. Issue 25 (14th June 2018) - Han, Bingyan; Li, Ying; Peng, Tingting; Yu, Mingbo; Hu, Xixi; He, Gaohong
Abstract : Synthesizing CDs directly derived from PEI and their application for the detection of Co 2+ . Abstract : In this paper, polyethyleneimine (PEI) was applied as a carbon source for synthesizing fluorescent carbon dots (CDs) through a facile and one-step hydrothermal route. Both the N-doping and the amino-functionalization of CDs were accomplished simultaneously. The CDs exhibited strong blue fluorescence and good dispersion in aqueous solution. A large number of amino groups on the surface of CDs greatly simplified the subsequent modification steps. Through an amide reaction, glutathione-functionalized CDs were successfully applied to the selective detection of Co 2+, in the linear range from 2.0 × 10 −5 to 1.0 × 10 −4 mol L −1 .